THE EFFECT OF INTERACTIONAL STRATEGY TRAINING ON PEER COLLBORATION AND INTERACTION PATTERNS - Tosun, Sibel; Alagozlu, Nuray (My University, 2023)
This study aims to examine the impact of interactional strategy training on dyadic interaction patterns during peer interaction. 28 undergraduate students between the ages of 18 and 22 participated in the study. The participants consisted of two groups: the experimental group, which received interactional strategy training, and the control group, which performed the same pair tasks as the experimental group but did not receive strategy training. The study employed a mixed-methods research design collecting quantitative and qualitative data through pre-, post- and delayed-post speaking tasks, self-evaluation forms, and semi-structured interviews. Transcripts of pre-, post-, and delayed-post tasks were analyzed to identify interaction patterns and enumerate the interaction strategies used by the dyads. Analysis of dyadic interaction reveals that training in interactional strategies improves the quality of peer interaction and leads to a shift from non-collaborative to collaborative interaction when performing pair tasks. Analysis of the self-evaluation forms and interviews shows that participants in the strategy group benefited greatly from the strategy training and gained a heightened awareness of their interactional behaviors. Participants also reported improvements in their fluency, interaction skills, strategy use, and affective states such as motivation, confidence, and self-esteem.
Keywords: Peer interaction; Interactional Strategies; Patterns of interaction; Collaborative interaction; Strategy training